EXPERIMENTAL DESIGN OF AN INTEGRAL BACKSTEPPING CONTROL FOR A SINGLE-PHASE SHUNT ACTIVE POWER FILTER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
In this work, a cascaded two-loops nonlinear integral-backstepping based control has been derived for single-phase shunt active power filter to improve harmonic mitigation, reactive power compensation and dc-link voltage regulation. Two loops non-linear controllers based on an Integral-backstepping strategy is developed which is robust and stable in a wide range of output current and DC-link voltage changes. First, the model of the single-phase shunt active power filter is exposed. Then, an integral backstepping control strategy applied to current loop is developed to provide global control robustness. Moreover, the compensation control system is then supported by an another integral backstepping controller for DC-link voltage control in order to enhance DC-link loss compensation capability and to generate the required active power which should be taken by the SAPF from the power supply. Designed active power filter control has been implemented using Dspace 1103. The practical response of the developed controller is studied in some test; it is shown that the proposed controller is able to eliminate harmonic components of the local load current with a fast dynamic response.
Keywords: Power Quality, Active Power Filter, Backstepping Control